Otorhinolaryngology - Slouka, David (Galén Publishing House, 2018)
In this book, otorhinolaryngology is presented to students as a medical branch, individual chapters deal with particular "sub-branches" and common fields of medicine with other medical specializations.
Keywords: Otolaryngology; otorinolaryngologie